تراكيب الدعاء في القرآن الكريم -دراسة لغويّة- - النجادات, نايف محمّد (مجلة جامعة القدس المفتوحة للبحوث الإنسانية والاجتماعية, 2022)
الملخص باللغة العربية: هذا بحث لغويّ في تراكيب الدعاء في صدر الإسلام؛ وهو محاولة لعرض‏ التراكيب النحوية للأدعية والتحايا وأساليبها، فقد تطورت التراكيب والأساليب اللغوية للدعاء بسبب تأثير الفكر الإسلامي المتضمن في القرآن الكريم. وقد تبيّن أنّ تراكيب الدعاء استمرت عند العرب في بداية عصر صدر الإسلام، ثمّ تلاشت تدريجيا تراكيب الدعاء والتحية المناقضة للفكر الإسلامي، وظهرت أدعية وتحايا تتوافق مع فكر العقيدة الإسلامية. Abstract Structures of supplication among pre-Islamic Arab and in the Holy Quran. This is a linguistic research on the structures of supplication in early Islam. It is an attempt to present the grammatical structures of the supplications and the supplications and their methods. The linguistic structures and methods of supplication developed due to the influence of Islamic thought included in the Holy Quran. It was found that the structures of supplication persisted among the Arabs at the beginning of the era of early Islam, then gradually the structures of supplication and greetings that contradicted the Islamic thought disappeared, and supplications and greetings appeared in line with the thought of the Islamic faith.